2010
DOI: 10.1074/jbc.m109.053843
|View full text |Cite
|
Sign up to set email alerts
|

Protein Phosphatase 2A Regulates Interleukin-2 Receptor Complex Formation and JAK3/STAT5 Activation

Abstract: Reversible protein phosphorylation plays a key role in interleukin-2 (IL-2) receptor-mediated activation of Janus tyrosine kinase 3 (JAK3) and signal transducer and activator of transcription 5 (STAT5) in lymphocytes. Although the mechanisms governing IL-2-induced tyrosine phosphorylation and activation of JAK3/STAT5 have been extensively studied, the role of serine/threonine phosphorylation in controlling these effectors remains to be elucidated. Using phosphoamino acid analysis, JAK3 and STAT5 were determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 59 publications
1
32
1
Order By: Relevance
“…Protein phosphatase (PP)2A has been implicated in promoting IL-2R signaling in the YT cell line through its ability to dephosphorylate serine and threonine residues in IL-2Rb, JAK3, and STAT5 (20). Therefore, we tested whether the PP1/PP2A inhibitor calyculin A affected IL-2-dependent pSTAT5 activation in various populations of primary human T cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Protein phosphatase (PP)2A has been implicated in promoting IL-2R signaling in the YT cell line through its ability to dephosphorylate serine and threonine residues in IL-2Rb, JAK3, and STAT5 (20). Therefore, we tested whether the PP1/PP2A inhibitor calyculin A affected IL-2-dependent pSTAT5 activation in various populations of primary human T cells.…”
Section: Resultsmentioning
confidence: 99%
“…Tregs express high levels of FOXP3-dependent microRNA miR-155 that lowers SOCS1 and enhances IL-2R signaling (32). Another mechanism may be related to the levels of serine/threonine phosphorylation associated with IL-2Rb, JAK3, and STAT5, where this modification downregulates IL-2R signaling (20). Indeed, we showed that inhibition of the serine/threonine phosphatase activity with calyculin A, which targets PP1 and PP2A, highly inhibited IL-2-dependent pSTAT5 at low doses of IL-2 in Tregs.…”
Section: Discussionmentioning
confidence: 99%
“…For example, aberrant activation of the JAK/ STAT pathway is associated with numerous human malignancies, 38 and PP2A negatively regulates the activating phosphorylation of JAK3 and STAT5 in the context of IL-2 stimulation. 39 Likewise, PP2A regulates the major signaling pathway, Ras/Raf/ MEK/ERK, by directly associating with ERK2 and MEK1 and indirectly with Ras and Raf. [40][41][42][43] Constitutive activation of the Ras/Raf/MEK/ERK pathway has been well characterized in malignant transformation of susceptible cells.…”
Section: Inhibition Of Wnt/beta-catenin Signalingmentioning
confidence: 99%
“…In addition, a reduction in protein migration was observed in the sample stimulated with IL-2 as well as in the CA-treated sample (Fig. 1B, lanes b and c, bottom panel), a phenomenon observed frequently in phosphorylated proteins (18). The bands corresponding to non-stimulated (75-kDa), IL-2-stimulated (80-kDa), and CA-treated (100-kDa) IL-2R␤ (Fig.…”
Section: Resultsmentioning
confidence: 95%
“…Inhibition of protein phosphatase type 2A (PP2A) diminishes STAT3, STAT6, STAT5, JAK3, and IL-2R␤ activation (18, 24 -26). Serine phosphorylation of STAT5, JAK3, and IL-2R␤ was enhanced, whereas IL-2-induced tyrosine phosphorylation was attenuated (18).…”
mentioning
confidence: 92%